2015
DOI: 10.4258/hir.2015.21.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Usability of Academic Electronic Medical Record Application for Nursing Students' Clinical Practicum

Abstract: ObjectivesNursing curricula for undergraduate nursing students need to reflect the information technology used in current nursing practice. A smart-device Academic Electronic Medical Record (AEMR) application can help nursing students access and document records for the clinical practicum. We conducted a pilot study to evaluate the usability of an AEMR application before applying it to the clinical nursing practicum.MethodsA previously developed EMR application was modified as an AEMR to access patient informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…A nursing training program in Korea used a mobile application to allow students to access an academic electronic medical record, a separate space for students to practice the documentation. The researchers concluded that this strategy provided students with more opportunities to practice on medical documentation [ 16 ]. A study in 1999 reviewed a self-directed learning program [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A nursing training program in Korea used a mobile application to allow students to access an academic electronic medical record, a separate space for students to practice the documentation. The researchers concluded that this strategy provided students with more opportunities to practice on medical documentation [ 16 ]. A study in 1999 reviewed a self-directed learning program [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The research under this topic then focuses on the evaluation of medical information systems in different situations, not only including the considerations of system implementation, such as availability, feasibility, cost, benefit, time, workflow, but also the impact on the nursing quality, such as reducing medical errors, reducing medication errors, and improving patient prognosis. With the development and maturity of the application of the medical system, EHRs began to be used in medical education, such as the application of the academic electronic medical record (AEMR) system to improve nursing students' grasp of health care decision-making and nursing informatics [89].…”
Section: Information Systems Application and Impactmentioning
confidence: 99%
“…While some health information technology (IT) research presents usability evaluations of documents that capture clinical information, 18 we did not find any literature that evaluates the usability of sharing clinical documents via secure messaging. Such evaluation is important, because secure messaging could be useful for a wide range of clinical documents, including a patient's treatment plan, medications, imaging studies, and laboratory reports.…”
Section: Background and Significancementioning
confidence: 81%